Strategic leadership practices in emerging economies: a systematic review and empirical investigation - Debebe Alemu Kebede; Shimelis Zewdie Werke; Taye Amogne Kebede (Cogent Business & Management, 2024)
Research on strategic leadership practices in emerging economies is crucial due to increasing global influence. This study explores strategic leadership by addressing four key research questions using an integration approach. The first three questions are answered through a systematic review, while the fourth is explored through an empirical study. A total of 27 journal articles were selected based on strict inclusion and exclusion criteria, and were analyzed using content analysis, while empirical data were analyzed descriptively. The majority of reviewed literature related the concept of strategic leadership with executives' functions that have strategic consequences. Whereas factors contributing to ineffective strategic leadership include short-termism, hubris, greed, and unethical behavior. The empirical study revealed that Ethiopian higher education institutions positively view institutional innovativeness, information management, strategic decision-making, and HRM activities. However, priority management, strategic control, ethical leadership, strategic influence, and stakeholder engagement were less favorably regarded. Strategic leadership in emerging economies, including Ethiopian higher education institutions, is shaped by both universal leadership principles and context-specific challenges. To thrive, strategic leaders must balance immediate pressures with long-term organizational vision, focusing on innovation, ethical practices, and robust stakeholder engagement. As well as the study inform leadership development, global business strategies, and supports sustainable economic growth in emerging markets.
Keywords: 650; Strategic leadership; emerging economy; higher education; incompetency; systematic review; integrative approach